Röd pandas (Ailurus fulgens) hägnutnyttjande och sociala beteenden på Parken Zoo - Sidstedt, Elin (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
The red panda (Ailurus fulgens), also called red cat-bear or lesser panda is a threatened species due to human destruction of the environment the panda is living in. The red panda is the only species in the family Ailuridae, since they can neither be in the same family as bears or raccoons, but they do belong in the same superfamily as the raccoon. They are classified as carnivores but their diet mainly consists of bamboo. The red panda lives in the foot of the Himalayas in subtropical and temperate forests. They live on an altitude of around 3000 meters close to water and can often be found in winter green trees. The red panda is a solitary animal outside the breeding season but they can live in family groups and in pairs. They can communicate with different kind of sound signals that could sound like birds singing, whistles and high pitch screams. They also have aggressive sounds like growling, hissing and snorting. The panda also communicates by scent marking. They do not spend much time on social behaviours as play, all grooming or aggressive behaviours. The aim of this study was to see how the red pandas utilise their enclosure, what kind of social behaviour they perform and also if the two of them are connected. To investigate this an ethological study was conducted on three red pandas at Parken Zoo in Eskilstuna, Sweden. Enclosure utilisation was studied with scan sampling with an interval of 1 minute and social behaviour with behaviour observation where every social behaviour was noted. Both methods were used at the same time during four hours a day for ten days during 14-15 April. The pandas in this study spend most of their time in trees and especially one tree, a tree which at the time of the study had no leafs. The second most used tree was a pine tree which hade pine needles and it was a surprise the pandas did not prefer that tree. They did not perform much social behaviours and the behaviour performed most was scent marking. At two occasions the pandas interacted with each other by body contact and made aggressive sound signals toward each other. It is not possible to see any connection between enclosure utilisation and social behaviour. But it is possible to see a tendency that the social behaviour occurs in trees, which is probably due to the pandas spending so much of their time in in the trees.